2018
DOI: 10.26804/ager.2019.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Microbial improved and enhanced oil recovery (MIEOR): Review of a set of technologies diversifying their applications

Abstract: Microbial improved and enhanced oil recovery (MIEOR) deploys microbes into wellbores and subsurface oil reservoirs and/or stimulates in-situ microbes to generate biochemicals that induce positive changes to reservoir and/or fluid conditions. MIEOR has a history of laboratory testing and field trials stretching back many decades, but few large-scale commercial projects. This review describes mechanism and components involved and the challenges in scaling-up laboratory performance to field-wide commercial applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 87 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…This water flows laterally to increase the sweeping efficiency of the crude oil (reducing the residual oil saturation), and help to manage excess water production. The microbial consortium clusters can disappear and displace during water flooding, causing a dynamic stimulation of new flow channels [50][51][52]. The strategy of this stage is to characterize microbial communities and to understand their cultivation methods.…”
Section: Microbial Methods (Meor)mentioning
confidence: 99%
See 1 more Smart Citation
“…This water flows laterally to increase the sweeping efficiency of the crude oil (reducing the residual oil saturation), and help to manage excess water production. The microbial consortium clusters can disappear and displace during water flooding, causing a dynamic stimulation of new flow channels [50][51][52]. The strategy of this stage is to characterize microbial communities and to understand their cultivation methods.…”
Section: Microbial Methods (Meor)mentioning
confidence: 99%
“…In addition, a negative perception exists regarding the use of microbes, although the tests carried out by laboratories have proven these to be safe [60,156]. Numerous other factors are currently contributing to the lack of attention being paid to this approach [11,12,22,36,42,51,55,64,74,154,163]. Its limitation and benefits are listed in Figure 7.…”
Section: A Vast Chronicle Of Meor History and Case Studiesmentioning
confidence: 99%
“…Microbial improved and enhanced oil recovery (MIEOR) deploys microbes into wellbores and subsurface oil reservoirs and/or stimulates in-situ microbes to generate biochemicals that induce positive changes to reservoir and/or fluid conditions. 194 Although microbial has not been widely used in the oil industry, it is shown to be feasible in a number of laboratory experiments and field trials. 195 Armstrong et al showed that microbial could produce a biosurfactant and bioclogging in water-wet micromodels.…”
Section: Low-salinitymentioning
confidence: 99%
“…After primary and secondary production, up to 85% of the oil remains in the reservoir [23]. Microbial improved and enhanced oil recovery (MIEOR) is one of the secondary and tertiary methods to increase the oil production using microorganisms [35]. Bioplug technology is a MIEOR strategy that consists in plugging the most permeable zones in the reservoir, which provokes water to flow through new paths and recovering the oil in these new zones.…”
Section: Introductionmentioning
confidence: 99%